Effect of radiotherapy exposure on fruquintinib plus sintilimab treatment in refractory microsatellite stable metastatic colorectal cancer: a prospective observation study - Jing Wang; Tao Zhang; Lei Zhao; Min Jin; Pindong Li; Shengli Yang; Hong Ma; Zhenyu Lin; Junli Liu; Hongli Liu; Kunyu Yang; Dandan Yu; et al. (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitors (ICIs) in combination with antiangiogenic drugs have shown promising outcomes in the third-line and subsequent treatments of patients with microsatellite stable metastatic colorectal cancer (MSS-mCRC). Radiotherapy (RT) may enhance the antitumor effect of immunotherapy. However, the effect of RT exposure on patients receiving ICIs and targeted therapy remains unclear. This study aimed to investigate the association between RT exposure and clinical responses to fruquintinib (a highly selective tyrosine kinase inhibitor of vascular endothelial growth factor receptor) plus sintilimab (an anti-programmed death 1 antibody; F&S) in previously treated patients with MSS-mCRC and to explore predictive biomarkers.Methods In this prospective observational study, patients with mCRC receiving F&S as third-line or subsequent treatment were enrolled. Eligible patients were divided into the RT cohort (RTC) and the non-RT cohort (NRTC) according to their RT history. The primary endpoint was the objective response rate (ORR). Secondary endpoints included disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety. Pretreatment fecal and serum samples were collected for microbiome analysis, metabolome analysis, and immune signatures to identify biomarkers for treatment.Results A total of 55 patients were included, of which 25 were in the RTC and 30 in the NRTC. Better ORR (28.0% vs 6.7%, p=0.048), DCR (80.0% vs 36.7%, p=0.002), median PFS (6.2 vs 2.7 months, p<0.001), and median OS (14.8 vs 5.9 months, p=0.019) were noted in patients with RTC than those with NRTC. The enrichment of Lactobacillus, Bifidobacterium, and PC(20:5(5Z,8Z,11Z,14Z,17Z)/20:3(8Z,11Z,14Z)) in RTC significantly predicted better DCR and PFS, whereas guanosine and interleukin-10 predominated in patients with NRTC were negatively correlated with PFS and OS.Conclusions Patients with RT exposure benefited significantly from F&S in the third-line or subsequent treatment for MSS-mCRC. Gut microbiota, metabolites, and cytokines may help predict F&S outcomes for mCRC, which may be helpful in treatment decision-making.Trial registration number ClinicalTrials.gov identifier: NCT05635149.